Rancang Bangun Sistem Administrasi Surat Keluar Masuk Berbasis Web Di Kantor Kecamatan Margomulyo - Danang Rudy Purnomo; Romzi Hamid; Inung Diah Kurniawati (Buletin Ilmiah Informatika Teknologi, 2023)
Letters are a formal communication media used in agencies, companies and organizations to internal and external parties. In Margomulyo District, the administration of correspondence still uses the manual method. Especially at the time of incoming and outgoing letters and dispositions. The disposition process requires a relatively long time, which is because the camat is often out on duty, besides that there are some missing letters due to the limited knowledge of employees in archiving letters. With this system, it is hoped that it can accelerate the disposition process and store archives digitally. Our goal in making this system is to be able to overcome some of the problems that arise, including the long disposition process and some missing letters. The method used in the development of this system we use the Rapid Application Development method, which allows faster system development. A web-based administration system for incoming and outgoing mail at the Margomulyo District Office, is made using several programming languages, namely: HTML, PHP, CSS, and Javascript, while the database uses MySQL. In system testing using black box testing which only tests software functionality, the test shows valid results and no errors or bugs occur